ENERGETICS OF LOW-TEMPERATURE POLYMORPHS OF MANGANESE DIOXIDE AND OXYHYDROXIDE - Fritsch S.; Navrotsky A.; Post J.E. (My University, 1997)
Transposed temperature drop calorimetry at 977 K was used to study the energetics of natural manganese dioxides (pyrolusite and ramsdellite) and oxyhydroxides (manganite and groutite). The structures of these minerals are composed of MnO6 octahedra which share edges and/or corners to form a framework structure containing tunnels of different size. Appropriate thermodynamic cycles were used to determine the relative energetic stability of the polymorphs, with respect to each other and to bixbyite, Mn2O3. The enthalpy difference between these tunnel-structure manganese oxides is very small, ramsdellite is higher in enthalpy than pyrolusite by 5.4 ± 3.1 kJ/mol for MnO2 and groutite is metastable in enthalpy with respect to manganite by 1.7 ± 1.7 kJ/mol for MnOOH. These small differences suggest that the framework stability is probably governed by the nature of the MnO bonding rather than the openness of the structure. Furthermore, the very small energetic differences are consistent with the widespread occurence of metastable manganese oxides and oxyhydroxides in the natural environment, in minerals, and in technological processes.